Establishing the European Norm for the health-related quality of life domains of the computer-adaptive test EORTC CAT Core. (January 2019) - Liegl, G.; Petersen, M.A.; Groenvold, M.; Aaronson, N.K.; Costantini, A.; Fayers, P.M.; Holzner, B.; Johnson, C.D.; Kemmler, G.; Tomaszewski, K.A.; Waldmann, A.; Young, T.E.; et al.
Abstract: Objective: The computer-adaptive test (CAT) of the European Organisation for Research and Treatment of Cancer (EORTC), the EORTC CAT Core, assesses the same 15 domains as the EORTC QLQ-C30 health-related quality of life questionnaire but with increased precision, efficiency, measurement range and flexibility. CAT parameters for estimating scores have been established based on clinical data from cancer patients. This study aimed at establishing the European Norm for each CAT domain based on general population data. Methods: We collected representative general population data across 11 European Union (EU) countries, Russia, Turkey, Canada and the United States (n ≥ 1000/country; stratified by sex and age). We selected item subsets from each CAT domain for data collection (totalling 86 items). Differential item functioning (DIF) analyses were conducted to investigate cross-cultural measurement invariance. For each domain, means and standard deviations from the EU countries (weighted by country population, sex and age) were used to establish a T-metric with a European general population mean = 50 (standard deviation = 10). Results: A total of 15, 386 respondents completed the online survey (n = 11, 343 from EU countries). EORTC CAT Core norm scores for all 15 countries were calculated. DIF had negligible impact on scoring. Domain-specific T-scores differed significantly across countries with small to medium effect sizes. Conclusion: This study establishes the official European Norm for the EORTC CAT Core. The European CAT Norm can be used globally and allows for meaningful interpretation of scores. Furthermore, CAT scores can be compared with sex- and age-adjusted norm scores at a national level within each of the 15 countries. Highlights: This study establishes the official European Norm for the computer-adaptive test EORTC CAT Core based on 15, 386 persons. The European CAT Norm can be used globally and allows for meaningful interpretation of scores derived from EORTC CAT Core. EORTC CAT Core scores can also be compared with sex- and age-adjusted norm scores at national levels of 15 included countries.